Evaluation of Cholinergic Deficiency in Preclinical Alzheimer's Disease Using Pupillometry. (16th August 2017) - Frost, Shaun; Robinson, Liam; Rowe, Christopher C.; Ames, David; Masters, Colin L.; Taddei, Kevin; Rainey-Smith, Stephanie R.; Martins, Ralph N.; Kanagasingam, Yogesan
Abstract : Cortical cholinergic deficiency is prominent in Alzheimer's disease (AD), and published findings of diminished pupil flash response in AD suggest that this deficiency may extend to the visual cortical areas and anterior eye. Pupillometry is a low-cost, noninvasive technique that may be useful for monitoring cholinergic deficits which generally lead to memory and cognitive disorders. The aim of the study was to evaluate pupillometry for early detection of AD by comparing the pupil flash response (PFR) in AD (N = 14 ) and cognitively normal healthy control (HC, N = 115 ) participants, with the HC group stratified according to high (N = 38 ) and low (N = 77 ) neocortical amyloid burden (NAB). Constriction phase PFR parameters were significantly reduced in AD compared to HC (maximum acceleration p < 0.05, maximum velocity p < 0.0005, average velocity p < 0.005, and constriction amplitude p < 0.00005 ). The high-NAB HC subgroup had reduced PFR response cross-sectionally, and also a greater decline longitudinally, compared to the low-NAB subgroup, suggesting changes to pupil response in preclinical AD. The results suggest that PFR changes may occur in the preclinical phase of AD. Hence, pupillometry has a potential as an adjunct for noninvasive, cost-effective screening for preclinical AD.